MEMBANGUN BUDAYA SANTRI SADAR PAJAK MELALUI INKLUSI PAJAK GUNA MEMPERSIAPKAN GENERASI EMAS SADAR PAJAK SEJAK DINI DI LINGKUNGAN PONDOK PESANTREN DAARUL HUSNA KUDUS - Yunita Lisnaningtyas Utami; Nur Fani Arisnawati; Muhammad Izzat Firdausi (CV. Denasya Smart Publisher, 2025)
This community service activity was held in the Darul Husna Islamic Boarding School environment in Kudus, Central Java, Indonesia. The problem found was that tax inclusion-based learning had not been implemented as a national program integrated with subjects. The solution provided was to carry out socialization to transfer knowledge about taxation to build a culture of tax awareness from an early age. The implementation method was carried out by conducting socialization. The results of the socialization activity were to provide knowledge and inspiration to students at the Darul Husna Kudus Islamic Boarding School. That providing tax knowledge from an early age to students can build awareness of the importance of taxes. This can dig deeper into the enthusiasm of students to be more aware of the importance of tax obligations. Students become more aware that their daily activities are never free from taxes. Although they have not been officially registered as taxpayers, indirectly their activities are also related to taxation.